The Effect of Enterprise Risk Management and Environmental Disclosure on Firm Value with Good Corporate Governance as a Moderating Variable - Kristiyanto, Kristiyanto; Rosini, Iin; Kusumaningsih, Ani (UNIB Press, 2025)
This study aims to examine the influence of Enterprise Risk Management (ERM) and Environmental Disclosure on firm value, and the moderating effect of Good Corporate Governance (GCG). The research adopts a quantitative approach using panel data regression. The sample consists of 20 mining companies listed on the Indonesia Stock Exchange (IDX) during 2019–2024. Variables were measured using COSO for ERM, GRI 300 for Environmental Disclosure, and independent board proportion for GCG. Environmental Disclosure has a significant positive effect on firm value, whereas ERM does not show a significant effect. GCG significantly moderates the effect of ERM on firm value, but not the effect of Environmental Disclosure This study integrates ERM, environmental disclosure, and corporate governance in the mining sector context with a moderating variable approach. It contributes empirically by exploring the role of GCG in enhancing the value impact of ERM and environmental transparency. Firms should enhance environmental transparency and apply structured risk management supported by effective governance to improve firm value.